APLIKASI AIR KELAPA MUDA DALAM MENINGKATKAN PERTUMBUHAN BIBIT PISANG BARANGAN (Musa paradisiaca) - ENNY MUTRYARNY (Universitas Lancang Kuning, 2007)
ABSTRAKMany kinds of banana are cultivated in Indonesia but only parts of them have export prospectssuch as Barangan banana because it has more special qualities compared with other banana×s.The big problem faced in growing Barangan banana is that the seed is rarely found because ofsome factors : limited number of shoots cultivated to be seeds, slow growth, and heterogenous.Cultivation by using belahan bonggol is potentially to be developed because bonggol has manyeye-buds but its growth is various. Therefore, it is necessary to have efforts to increase thegrowth of the eye-buds. One of the alternative is providing natural plant growth regulators, thatis water of young coconut fruit containing sitokinin activity. It aims to study the level of ripeningsuitable concentration of water of young coconut fruit toward the growth of belahan bonggolseeds of barangan banana. The experiment shows that providing water of young coconut fruitwith concentration 100% can increase the growth of barangan banana seeds in the various levelof ripening eye-buds, and the excellent growing happens in the level of ripe eye-buds.